Humanisasi Pengemis dalam Perspektif Yusuf al-Qaradhawi - Miftah Fauzi; Suadi Sa`ad; Ade Fakih Kurniawan (Jurnal Keislaman, 2025)
The phenomenon of beggars is a complex social problem, especially in a country with a Muslim majority. Islam views poverty as a problem that must be overcome with the principles of social justice and economic empowerment. This study aims to examine Yusuf al-Qadawi's thoughts on the humanization of beggars from an Islamic perspective, which includes the empowerment of beggars, the role of the state in the fair distribution of wealth, and social rehabilitation approaches. This study uses a literature study method by analyzing books, articles, and scientific works that discuss al-Qardawi thought and social justice in Islam. The results of the study show that al-Qardawi emphasizes the empowerment of beggars through skills training and the provision of business capital, not just material assistance. Al-Qardawi also proposed that the state play a role as a facilitator in the policy of equitable distribution of wealth, to reduce social inequality and provide economic opportunities to the poor. This study concludes that al-Qardawi thought provides a sustainable solution in overcoming poverty by prioritizing empowerment and social integration. This approach shows that Islam offers practical solutions to social problems with more holistic principles of social justice and empowerment.